2021
DOI: 10.1002/ctm2.459
|View full text |Cite
|
Sign up to set email alerts
|

S100A7 as a potential diagnostic and prognostic biomarker of esophageal squamous cell carcinoma promotes M2 macrophage infiltration and angiogenesis

Abstract: 1. Elevated S100A7 in tumor tissues and serum samples of ESCC patients suggest a role as a biomarker. 2. A novel and promising diagnostic model for ESCC based on serum S100A7, SCC, and crfra21-1 was established.3. S100A7 promotes tumor progression by activating oncogenic pathways and remodeling tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
(83 reference statements)
3
30
0
Order By: Relevance
“…It has been shown that activation of S100A7-regulated pathways is linked to increased cancer-associated angiogenesis [ 30 ], the promotion of M2 macrophage infiltration in the tumor microenvironment [ 31 ] and enhancement of tumorsphere growth [ 1 ]. Furthermore, the upregulated excretion of S100A7 protein in serum and urine was reported in individuals with cancers such as esophageal squamous cell carcinoma [ 31 ], cutaneous melanoma [ 32 ] and bladder squamous cell carcinoma [ 33 ], suggesting S100A7 might be a potential diagnostic and prognostic biomarker in cancers. These observations corroborate our current results, showing that S100A7 was highly expressed in most investigated tumors, and that a high S100A7 expression was associated with poor prognosis in most tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of S100A7-regulated pathways is linked to increased cancer-associated angiogenesis [ 30 ], the promotion of M2 macrophage infiltration in the tumor microenvironment [ 31 ] and enhancement of tumorsphere growth [ 1 ]. Furthermore, the upregulated excretion of S100A7 protein in serum and urine was reported in individuals with cancers such as esophageal squamous cell carcinoma [ 31 ], cutaneous melanoma [ 32 ] and bladder squamous cell carcinoma [ 33 ], suggesting S100A7 might be a potential diagnostic and prognostic biomarker in cancers. These observations corroborate our current results, showing that S100A7 was highly expressed in most investigated tumors, and that a high S100A7 expression was associated with poor prognosis in most tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the interaction between S100 Ca 2+ -binding proteins and RAGE promotes tumor progression also stimulating invasive effects [ 44 , 66 69 ], we next aimed to explore whether S100A8/A9-RAGE activation prompts the migration of TNBC cells. S100A8/A9 treatment stimulated migratory effects in TNBC cells overexpressing RAGE, however these responses were reduced targeting either RAGE or FAK and by knocking-down the expression of the YAP/TEAD target FLNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It had been reported that LOR and FLG were abnormally upregulated in atopic dermatitis, which played a critical role in disease development [ 24 ]. It has been well known that OLP is a hyperkeratotic mucosal disease, and recently, researchers have found that the expression of filaggrin and filaggrin-2 markedly increased in OLP patients [ 25 ], which might suggest that filaggrin is essential to keratinization. Our findings about FLG also provide strong evidence for this viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…S100A7, s100 calcium binding protein A7, is a member of S100 protein family. Researchers have found that it was abnormally upregulated in esophageal squamous cell carcinoma (ESCC), which might promote tumor progression by impacting M2 macrophage infiltration and angiogenesis; thereby, S100A7 was expected to act as a therapeutic target for ESCC treatment [ 25 ]. Moreover, based on whole gene expression profiling, it had been identified as a novel candidate biomarker related to OSCC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%